2021
DOI: 10.1007/s40821-020-00177-3
|View full text |Cite
|
Sign up to set email alerts
|

The US–Ireland–India in the catch-up cycles in IT services: MNCs, indigenous capabilities and the roles of macroeconomic variables

Abstract: This study attempts to explain successive changes in industrial leadership in IT services by employing the catch-up cycle theory developed by Lee and Malerba (Res Policy 46(2):338-351, 2017). A catch-up cycle was observed in which leadership have changed from the US to Ireland and subsequently to India. Currently, there is now a `coexistent leadership` in which both India and Ireland share the leadership position since Ireland has recently recovered some of its market shares. The research has two main contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…Therefore, the outcomes of this study strongly support the hypothesis that mobility offers firms and nations disadvantaged by geography, size, or historical circumstances a way to access the talent and knowledge necessary to kick-start or catch-up (Lee, 2019 ; Porto et al, 2021 ) and uplift productivity and economic conditions. As short-term mobility is relatively simple to implement vis-à-vis productivity channels that require large initial costs or expertise (e.g., R&D), it has the advantage of being a flexible and effective tool to access or share “sticky” productive knowledge.…”
Section: Conclusion and Managerial And Policy Implicationssupporting
confidence: 72%
“…Therefore, the outcomes of this study strongly support the hypothesis that mobility offers firms and nations disadvantaged by geography, size, or historical circumstances a way to access the talent and knowledge necessary to kick-start or catch-up (Lee, 2019 ; Porto et al, 2021 ) and uplift productivity and economic conditions. As short-term mobility is relatively simple to implement vis-à-vis productivity channels that require large initial costs or expertise (e.g., R&D), it has the advantage of being a flexible and effective tool to access or share “sticky” productive knowledge.…”
Section: Conclusion and Managerial And Policy Implicationssupporting
confidence: 72%
“…Interestingly, some scholars provide a theoretical framework and empirical evidence suggesting that there is also a prospective of catch-up and sustained success for latecomers in the following of a first wave of new technologies (Landini et al, 2017;Porto et al, 2021). Based on the catch-up cycle theory developed by Lee and Malerba (2017), Porto et al (2021) also observed a catch-up cycle in which the leadership can change from a country to another. Yet, some key technologies such as Artificial Intelligence (AI)-a new phase of the ICT revolution-or such as advanced biotech can represent the driver of a technological revolution for the EU.…”
Section: Randd Investment Performance Of Main Global Economic Areasmentioning
confidence: 99%
“…However, Landini et al (2017) show that in the successive changes in technology-driven industrial leadership different catch-up cycles emerge where latecomers could succeed. While it is difficult to know what the next revolution might be, some technology areas, such as environment, health care and Artificial Intelligence, can represent an opportunity for Europe to keep a leadership position in some strategic segments (Porto et al, 2021).…”
Section: Further Analytical Considerationsmentioning
confidence: 99%
“…An obvious gap in the literature exists regarding a possible job-creation effect in the supply side among developers of AI and robotics technologies conceived as product innovations in upstream sectors. Indeed, according to the Schumpeterian literature (see Schumpeter, 1912 ; Porto et al, 2021 ), technological change entails both labour-saving process innovation and product innovation. The introduction of new products (both in manufacturing and services) can give rise to new branches of production and create additional employment opportunities.…”
Section: Introductionmentioning
confidence: 99%